Women's Prose: Past, Present and Future - Novikova, Olga (Slavica, 2021)
The very expression "women's prose" in Russian literary discourse is debatable, since even many female writers refuse to identify themselves as such. A woman writer has all the rights of a writer, but she also has the additional right to self-identify as a representative of "women's prose". Women's prose requires a double research point of view: looking at it as an integral part of fiction and identifying the specific features of works created by women writers.    During the period of perestroika (the second half of the 1980s), women's activity in Russian prose became more active, and L. Petrushevskaya and T. Tolstaya came to the forefront of literary life. An important milestone in the awareness of the specifics of women's prose was the series "Women's Handwriting" by the publishing house "Vagrius". A characteristic trend in the development of modern Russian women's prose is the democratization of the artistic thinking and language, the attraction of high prose tothe mainstream, to mass nature and the feeling of accessibility. In this regard, the article examines the prose of V. Tokareva, O. Slavnikova, D. Rubina, M. Stepnova, N. Abgaryan, G. Yakhina and others.